Eomes function is conserved between zebrafish and mouse and controls left-right organiser progenitor gene expression via interlocking feedforward loops - Talbot, Conor D.; Walsh, Mark D.; Cutty, Stephen J.; Elsayed, Randa; Vlachaki, Eirini; Bruce, Ashley E. E.; Wardle, Fiona C.; Nelson, Andrew C. (Frontiers in Cell and Developmental Biology, 2022)
The T-box family transcription factor Eomesodermin (Eomes) is present in all vertebrates, with many key roles in the developing mammalian embryo and immune system. Homozygous Eomes mutant mouse embryos exhibit early lethality due to defects in both the embryonic mesendoderm and the extraembryonic trophoblast cell lineage. In contrast, zebrafish lacking the predominant Eomes homologue A (Eomesa) do not suffer complete lethality and can be maintained. This suggests fundamental differences in either the molecular function of Eomes orthologues or the molecular configuration of processes in which they participate. To explore these hypotheses we initially analysed the expression of distinct Eomes isoforms in various mouse cell types. Next we compared the functional capabilities of these murine isoforms to zebrafish Eomesa. These experiments provided no evidence for functional divergence. Next we examined the functions of zebrafish Eomesa and other T-box family members expressed in early development, as well as its paralogue Eomesb. Though Eomes is a member of the Tbr1 subfamily we found evidence for functional redundancy with the Tbx6 subfamily member Tbx16, known to be absent from eutherians. However, Tbx16 does not appear to synergise with Eomesa cofactors Mixl1 and Gata5. Finally, we analysed the ability of Eomesa and other T-box factors to induce zebrafish left-right organiser progenitors (known as dorsal forerunner cells) known to be positively regulated by vgll4l, a gene we had previously shown to be repressed by Eomesa. Here we demonstrate that Eomesa indirectly upregulates vgll4l expression via interlocking feedforward loops, suggesting a role in establishment of left-right asymmetry. Conversely, other T-box factors could not similarly induce left-right organiser progenitors. Overall these findings demonstrate conservation of Eomes molecular function and participation in similar processes, but differential requirements across evolution due to additional co-expressed T-box factors in teleosts, albeit with markedly different molecular capabilities. Our analyses also provide insights into the role of Eomesa in left-right organiser formation in zebrafish.